Novel report on SHG efficiency, Z-scan, laser damage threshold, photoluminescence, dielectric and surface microscopic studies of hybrid inorganic ammonium zinc sulphate hydrate single crystal. (August 2018) - Ramteke, S.P.; Baig, M.I.; Shkir, Mohd; Kalainathan, S.; Shirsat, M.D.; Muley, G.G.; Anis, Mohd
Graphical abstract: Highlights: Novel report exploring optical, dielectric and microscopic properties of AZSH crystal. SHG efficiency of AZSH crystal is 2.53 times higher than KDP. AZSH crystal delivers negative nonlinear refraction and saturable absorption at 632.8 nm. The order of n2, β and χ 3 is 10 −9 cm 2 /W, 10 −4 cm/W and 10 −4 esu respectively. Nd:YAG laser induced surface damage threshold of AZSH crystal is 345.57 MW/cm 2 . Abstract: Hybrid inorganic nonlinear optical crystals find huge applications in laser assisted photonic devices therefore present communication firstly aims to investigate the dielectric, microscopic and linear-nonlinear optical properties of ammonium zinc sulphate hydrate (AZSH) crystal. The inorganic AZSH complex has been synthesized and 15 × 10 × 09 mm 3 single crystal was grown by slow solvent evaporation method. The powder and single crystal X-ray diffraction technique has been employed to evaluate the crystalline phase and determine the structural parameters of AZSH crystal. The optical transparency of AZSH crystal has been examined within the wavelength rage of 200–1100 nm. The enhanced second harmonic generation efficiency of AZSH crystal is 2.53 times higher than standard KDP crystal. The laser damage threshold of AZSH crystal has been determined using the Nd:YAG laser operating at 1064 nm. The close and open aperture Z-scan studies have been performed to ascertain the nature of third order nonlinear optical (TONLO) refraction and absorption of AZSH crystal. The order of TONLO parameters n2, β and χ 3 is found to be 10 −9 cm 2 /W, 10 −4 cm/W, 10 −4 esu respectively. The AZSH crystal is found to have violet colored luminescence emission centered at 370 nm. The dielectric constant and dielectric loss of AZSH crystal has been evaluated within 30 Hz to 1 MHz. The chemical etching technique has been imposed to examine the growth habitat and determine the etch pit density of AZSH crystal.